Pendidikan Berbasis Kompetensi: Implikasinya pada Kurikulum dan Pembelajaran - Saaduddin Saaduddin (Journal on Education, 2022)
This article aims to explain the nature of competency-based education (CBE) by examining the concept of competency as an educational outcome and its implications for curriculum and instruction. Analysis of problems related to CBE and its application in learning is done by incorporating CBE concepts into curriculum design. Some of the consequences of implementing it in schools are also discussed. Each of the ideas put forward can be used as a frame of reference for determining the types of difficulties a school will face when a CBE-based curriculum is implemented.